Identification of two new genetic loci for high-resolution genotyping of Enterocytozoon bieneusi - Meng Xinan; Ou Yonglin; Jiang Wen; Guo Yaqiong; Xiao Lihua; Feng Yaoyu; Li Na (Parasite)
In addition to the ribosomal internal transcribed spacer (ITS) locus, four loci (MS1, MS3, MS4, and MS7) have been identified to develop multilocus sequence typing tools for high-resolution genotyping of Enterocytozoon bieneusi in previous studies. However, the use of only five loci was insufficient for population genetic analysis of E. bieneusi from diverse hosts. In this study, comparison of a clinical genome sequence (C44566) with the whole genome sequence of an E. bieneusi isolate (H348) in GenBank led to the selection of the hypothetical protein 1 (hp1) and tubulin 1 (tub1) loci. Further analysis of the two loci with 156 E. bieneusi-positive samples showed high sequence polymorphisms in ITS Groups 1–6 and 10. Altogether, 30 and 23 sequence types were identified at hp1 and tub1, respectively. Genotyping based on the two loci confirmed the lack of genetic differentiation between Group 1 and Group 2 genotypes, as previously reported. Moreover, the genotypes in Groups 4 and 5 are more divergent from other genotypes within Groups 1–10. However, isolates in Group 11 and 12 could not be amplified at the hp1 and tub1 loci, supporting the previous conclusion of genetic uniqueness of the two genotype groups. The identified genetic markers and generated data could be used to develop a multilocus sequence typing tool for high-resolution genotyping of E. bieneusi, which would also have implications for understanding the taxonomy of Enterocytozoon spp., the public health significance of E. bieneusi in animals, and sources of E. bieneusi infections in humans.